Parallel Hybrid Powertrain Design for Honda BeAT 110 eSP Scooter to Improve Energy Efficiency and Reduce Emissions - Virgawan Adrian Noes; Muhammad Hamid Ramdhan Nur; Muhammad Nurtanto (VANOS Journal of Mechanical Engineering Education, 2026)
The increasing demand for energy efficiency and emission reduction in urban transportation requires innovative powertrain solutions. This study aims to design and analyze a parallel hybrid powertrain system for the Honda BeAT 110 eSP Scooter. The methodology involves integrating a 3000W BLDC Hub motor on a custom-made 6mm steel bracket arm, coupled with a 60V 27Ah lithium battery, without altering the main frame structure. Performance testing was conducted using a chassis dynamometer and on-road testing to measure fuel consumption, torque, and emissions. The results demonstrate that the hybrid system significantly improves vehicle performance. Fuel efficiency increased to 92 km per charge/refuel combination (compared to 38 km in standard mode). The electric motor produced a peak torque of 81.93 Nm, which is three times higher than the conventional engine's torque of 25.48 Nm. Furthermore, exhaust emissions (CO and HC) were reduced to 0% when operating in electric mode. Despite a 24 kg weight increase, the center of gravity shift remained within safe limits. This research concludes that a modular parallel hybrid system is a viable and efficient solution for urban scooters.